2007
DOI: 10.1002/mc.20306
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adenomatous polyposis coli (APC) tumor supressor gene in human colon cancer cell lines on cell cycle arrest by apigenin

Abstract: This research assessed the importance of the adenomatous polyposis coli (APC) tumor suppressor mutation in the ability of apigenin to induce cell cycle arrest using HT29-APC cells, which contain inducible wild-type APC under the metallothionein promoter. HT29-GAL cells, containing beta-galactosidase (GAL), were included as control. Treatment with apigenin (0, 20, 40, 60, and 80 microM) for 48 h resulted in reduction in the cell number (P < 0.05) concurrent with flow cytometry results showing a dose-dependent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 24 publications
3
25
0
Order By: Relevance
“…43,44 Although many flavonoid members with apoptotic effects on the HT29 cell line have been studied, [45][46][47][48][49] the number of those tackling apigenin administration to HT29 cells remains limited. [48][49][50][51][52][53][54][55] Four of these studies evaluated the effect of apigenin on cell viability. Treatment with 40lM apigenin for 24 hours; 49 60 lM and 80lM apigenin for 48 hours; 43 40 lM, 60 lM, and 80 lM apigenin for 48 hours; 54 and 130.6.lM apigenin for 72 hours 55 all resulted in statistically significant reductions in cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Although many flavonoid members with apoptotic effects on the HT29 cell line have been studied, [45][46][47][48][49] the number of those tackling apigenin administration to HT29 cells remains limited. [48][49][50][51][52][53][54][55] Four of these studies evaluated the effect of apigenin on cell viability. Treatment with 40lM apigenin for 24 hours; 49 60 lM and 80lM apigenin for 48 hours; 43 40 lM, 60 lM, and 80 lM apigenin for 48 hours; 54 and 130.6.lM apigenin for 72 hours 55 all resulted in statistically significant reductions in cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin has also been reported to inhibit cell invasion by downregulation of COX-2 and MMP-2 expression and inhibit colon cancer cell growth through suppressing EGFR gene expression and modulating Akt/mTOR signaling in CRC cells [39][40][41]. In another study, curcumin has been found to Suppresses the phosphorylation of EGFR and downstream signaling in colon carcinoma cells [19] Induces apoptosis through upregulation of p53, p21, and AMPK signaling [20] Reduces b-catenin/Tcf transcriptional activity, induces G2/M cell-cycle arrest through decreasing gene expression of cyclin D1 and survivin [21] Apigenin Induces apoptosis by enhancing APC protein expression in colon cancer cells [22] Reduces AOM-induced ACF number and increases apoptosis of luminal surface colonocytes [23] 5-Hydroxy-6,7,8,4…”
Section: Chemopreventive Mechanisms Of Proanthocyanidin and Other Polmentioning
confidence: 99%
“…Apigenin, present in parsley and celery, evokes its inhibitory effect on carcinogenesis through the induction of apoptosis in human colon cancer cells and reduces azoxymethane (AOM)-induced ACF number in rats [22,23].…”
Section: Chemopreventive Mechanisms Of Flavonoids and Flavonolignan Omentioning
confidence: 99%
“…Pre-treatment with apigenin induces the apoptosis of HCT-116 colon cancer cells (5) and inhibits the growth of colon carcinoma cell lines, including SW480, HT-29 and Caco-2 (6). A previous study showed that apigenin enhanced apoptosis in HT29 cells with wild-type adenomatous polyposis coli (7). In vivo studies showed that apigenin moderately reduces azoxymethane-induced colon carcinogenesis and inhibits the growth of colorectal cancer (8).…”
Section: Introductionmentioning
confidence: 99%